2020
DOI: 10.5194/hess-24-349-2020
|View full text |Cite
|
Sign up to set email alerts
|

On the configuration and initialization of a large-scale hydrological land surface model to represent permafrost

Abstract: Abstract. Permafrost is an important feature of cold-region hydrology, particularly in river basins such as the Mackenzie River basin (MRB), and it needs to be properly represented in hydrological and land surface models (H-LSMs) built into existing Earth system models (ESMs), especially under the unprecedented climate warming trends that have been observed. Higher rates of warming have been reported in high latitudes compared to the global average, resulting in permafrost thaw with wide-ranging implications f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 66 publications
0
55
0
Order By: Relevance
“…In permafrost lowlands of the Taiga Plain, soil thawing has led to subsidence and inundation of ground surfaces resulting in extensive forest loss, fragmentation, and concomitant wetland expansion and conversion mostly to sphagnum-dominated bogs (Baltzer et al, 2014;Helbig et al, 2016). In the southern Arctic, increased permafrost thawing is leading to changes in channel permafrost conditions, increasing winter groundwater flow in the channel, and increasing occurrence of aufeis formation (Ensom et al, 2020). Many northern ecosystems are underlain by ice-rich permafrost that is highly sensitive to thawing during warm summers (Segal et al, 2016;Lewkowicz and Way, 2019) or following other disturbances (Williams et al, 2013).…”
Section: Permafrost Thaw As a Driver Of Landscape Change And Hydrological Reroutingmentioning
confidence: 99%
“…In permafrost lowlands of the Taiga Plain, soil thawing has led to subsidence and inundation of ground surfaces resulting in extensive forest loss, fragmentation, and concomitant wetland expansion and conversion mostly to sphagnum-dominated bogs (Baltzer et al, 2014;Helbig et al, 2016). In the southern Arctic, increased permafrost thawing is leading to changes in channel permafrost conditions, increasing winter groundwater flow in the channel, and increasing occurrence of aufeis formation (Ensom et al, 2020). Many northern ecosystems are underlain by ice-rich permafrost that is highly sensitive to thawing during warm summers (Segal et al, 2016;Lewkowicz and Way, 2019) or following other disturbances (Williams et al, 2013).…”
Section: Permafrost Thaw As a Driver Of Landscape Change And Hydrological Reroutingmentioning
confidence: 99%
“…The JMC and WH models were configured using the approach of Elshamy et al . (2020), where MESH was applied to three permafrost sites along the Mackenzie River valley.…”
Section: Model Configurationmentioning
confidence: 99%
“…Soil moisture memory was shown by Cosgrove et al (2003) and Rodell et al (2005) to be larger than thermal memory for shallow soil columns (2m and 3.5m), such that reaching a quasi-equilibrium state for moisture during spin-up requires more time than soil temperature, depending on soil characteristics. However, such conclusions may not be valid for deeper soil columns recommended for LSM simulation of permafrost, due to their larger thermal/hydraulic inertia (Sapriza-Azuri et al , 2018;Elshamy et al , 2020;Lamontagne-Hallé et al , 2020). For example, Elshamy et al (2020) showed that soil moisture stabilized faster than soil temperature in simulations for the Mackenzie River Basin using a 51.24m soil column.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations